The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1002/(sici)1097-4547(19980115)51:2<154::aid-jnr4>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of connexin32 in charcot‐marie‐tooth disease type X interfere with cell‐to‐cell communication but not cell proliferation and myelin‐specific gene expression

Abstract: Connexin32 (Cx32) is a gap junction protein and its mutations are responsible for X-linked Charcot-Marie-Tooth disease. We examined the functional abnormality of C6 glioma cells transfected with mutant (C53S and P172R) Cx32 genes. Nontransfected C6 did not express Cx32. Northern and Western blot analyses showed Cx32 mRNA and protein in cells with the wild-type gene as well as with the mutant Cx32 genes. An immunocytochemical study of cells with the wildtype gene showed the immunoreactive spots in the cell memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…However, mutations located close to the membrane‐cytoplasm interface, viz., E208K, Y211stop, R215W, R215Q, and R215stop, resulted in a dramatic reduction in gap junction functionality (Rabadan‐Diehl et al, 1994; Castro et al, 1999). Studies in transfected mammalian cell lines, which appear to possess more stringent intracellular trafficking requirements, have revealed other gross effects such as incorrect cellular localisation, e.g., G12S, R142W, and E208K (Deschenes et al, 1997; present study) and C53S and P172R (Yoshimura et al, 1998), and absence of staining at the plasma membrane, e.g., C60F, V139M, and R215Y (Omori et al, 1996). The oligomerisation properties of two of the above mutations, viz., G12S and E208K, have been rigorously examined in the present work.…”
Section: Discussionmentioning
confidence: 54%
“…However, mutations located close to the membrane‐cytoplasm interface, viz., E208K, Y211stop, R215W, R215Q, and R215stop, resulted in a dramatic reduction in gap junction functionality (Rabadan‐Diehl et al, 1994; Castro et al, 1999). Studies in transfected mammalian cell lines, which appear to possess more stringent intracellular trafficking requirements, have revealed other gross effects such as incorrect cellular localisation, e.g., G12S, R142W, and E208K (Deschenes et al, 1997; present study) and C53S and P172R (Yoshimura et al, 1998), and absence of staining at the plasma membrane, e.g., C60F, V139M, and R215Y (Omori et al, 1996). The oligomerisation properties of two of the above mutations, viz., G12S and E208K, have been rigorously examined in the present work.…”
Section: Discussionmentioning
confidence: 54%
“…27 Some mutations lead to a modification in trafficking of Cx-32 with a potential toxic cytoplasmic accumulation of the protein. 11,40 In the Xenopus oocyte model, Ressot et al 29 found that the effects of mutations of Cx-32 can be divided into two groups: those associated with a complete loss of function and those that retain the ability to form functional gaps but with altered voltage dependence and pH gating. The mutations localized in the regions that are essential to channel assembly and pore formation (transmembrane domains and second extracellular loop) produce nonfunctional channels.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the human Cx32 protein is depicted according to Yeager and Nicholson (1996). The consequences of the known CMTX mutations are shown schematically, along with the localization of 51 different Cx32 mutants in transfected mammalian cells (Deschênes et al, 1997;Martin et al, 2000;Omori et al, 1996;Yoshimura et al, 1998), 23 of which are from the present study. Note that colocalization studies with ER and Golgi markers were not performed on some of the mutations that have been reported to be retained intracellularly (Omori et al, 1996;Yoshimura et al, 1998); these are depicted as being retained in the ER, but they may be retained in the Golgi.…”
Section: Figmentioning
confidence: 97%